2021
DOI: 10.1016/j.envres.2020.110596
|View full text |Cite
|
Sign up to set email alerts
|

Meteorological factors, governmental responses and COVID-19: Evidence from four European countries

Abstract: With the global lockdown, meteorological factors are highly discussed for COVID-19 transmission. In this study, national-specific and region-specific data sets from Germany, Italy, Spain and the United Kingdom were used to explore the effect of temperature, absolute humidity and diurnal temperature range (DTR) on COVID-19 transmission. From February 1 st to November 1 st , a 7-day COVID-19 case doubling time (Td), meteorological factors with cumulative 14-day-lagge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 56 publications
0
36
0
2
Order By: Relevance
“…Additionally, Ladha et al added the number of COVID-19 tests into the linear regression (Ladha et al 2020 ). Fu et al entered the government response index and other factors into the distributed lag nonlinear models as independent variables (Fu et al 2021 ). However, only four studies identified potential confounding factors and conducted strategies to address the stated confounding factors, such as incorporations into the models and inclusions of dew point, cloud cover, precipitation, relative humidity, air pressure, or wind speed for the same period.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Ladha et al added the number of COVID-19 tests into the linear regression (Ladha et al 2020 ). Fu et al entered the government response index and other factors into the distributed lag nonlinear models as independent variables (Fu et al 2021 ). However, only four studies identified potential confounding factors and conducted strategies to address the stated confounding factors, such as incorporations into the models and inclusions of dew point, cloud cover, precipitation, relative humidity, air pressure, or wind speed for the same period.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 virus is a member of the coronavirus family “severe acute respiratory syndrome” (SARS) and exhibits flu-like symptoms (Fu et al 2021 ). Given that weather (temperature) is an important variable in predicting flu, it is likely to be a crucial factor for the transmissibility of COVID-19 as well (Sajadi et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that the lognormal distribution model had the best fit for the changes of COVID‐19 infected cases. Fu et al ( 2021 ) studied the influence of governmental responses and meteorological factors on COVID‐19 transmission in four European countries (UK, Italy, Germany, and Spain) using the distributed lag nonlinear model. Their results demonstrated that both the dry and cold environments are likely to facilitate COVID‐19 transmission.…”
Section: Environmental Variables and Transmission Of Sars‐cov‐2 Pandemicmentioning
confidence: 99%